2016
DOI: 10.1515/pjvs-2016-0069
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Acidity and Temperature of the Rumen and Abomasum in Diagnosing SARA in Dairy Cows after Calving

Abstract: The aim of the research was to determine the relationship between the acidity and temperature of the contents of the reticulorumen and abomasum in the first 10 days after calving and to evaluate these factors as predictive traits for the diagnosis of subclinical acidosis.The acidity and temperature of the contents of the reticulorumen and abomasum were measured using specific smaXtec boluses manufactured for animal care. According to the directions of the manufacturer, the boluses were inserted into the reticu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…Plaizier et al (2012) suggest that disorders associated with SARA could cause local inflammation of the rumen mucosa (rumenitis), which also increases the rectal temperature. Antanaitis et al (2016) showed that decrease of ruminal fluid pH during SARA increase the reticulorumen temperature which is correlated with the rectal temparature. Therefore, regular measurement of body temperature could be part of a routine systemic monitoring in cattle farms (Drillich et al 2001).…”
Section: Discussionmentioning
confidence: 95%
“…Plaizier et al (2012) suggest that disorders associated with SARA could cause local inflammation of the rumen mucosa (rumenitis), which also increases the rectal temperature. Antanaitis et al (2016) showed that decrease of ruminal fluid pH during SARA increase the reticulorumen temperature which is correlated with the rectal temparature. Therefore, regular measurement of body temperature could be part of a routine systemic monitoring in cattle farms (Drillich et al 2001).…”
Section: Discussionmentioning
confidence: 95%
“…In this situation, the free space antenna gain cannot be used for calculating the in-to-out-body path loss. In literature [11], [12] the antenna gains are included in the WBAN path loss calculation given by (1). Thus, the path loss including the antenna gains as a part of the channel model (P L incl ) is calculated as follows:…”
Section: Joint Antenna-channel:path Loss Difference For Body Loss mentioning
confidence: 99%
“…Monitoring health indicators in real time using sensors enables large dairy farms to optimize their profits as well as increase their cow welfare. Ruminal temperature and pH are important parameters to assess the nutritional and health status of dairy cows and to predict anomalies (e.g., metabolic disorders after calving) [1]. However, these parameters can be measured only using in-body sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Ruminal temperature and pH are important parameters to assess the nutritional and health status of dairy cows and to predict anomalies (e.g. metabolic disorders after calving) [1]. However, these parameters can be measured only by using in-body sensors.…”
mentioning
confidence: 99%
“…The low realised gain is due to the strong mismatch in the air (|S11| ≈ − 0.9 dB) since the antenna was specifically designed for in-body applications and relies on dielectric loading by tissues to achieve higher efficiencies [6]. The values of the realised gain in air and in-body were used to calculate the de-embedded antenna path loss (1). Finally, to model the path loss as a function of the TX-RX separation, a log-distance path loss model was used.…”
mentioning
confidence: 99%